(untitled) (European Journal of Pure and Applied Mathematics, 2010)
In this paper, we obtain existence and uniqueness results of IVP for set differential equations involving causal operators with memory. This paper is 2nd in sequel. In the first one we obtained inequality results and existence results for set causal operators involving memory.